Louise Imogen Guiney - Brown, Alice (Saga Egmont, 2022)
A study of American poet and essayist Louise Imogen Guiney, written by her colleague and friend Alice Brown. The pair traveled together to the English countryside in 1885 and become close. They were rumoured to have had a lesbian relationship together. Their friendship lasted until Guiney\'s death in 1920, and this biographical book was published by Brown in tribute to her friend in 1921. Alice Brown is an American novelist and short-story writer. She is best known for her tales about New England and as a writer that brings out the local colour in a place. Born in New Hampshire in 1857, Brown\'s stories often portray a female protagonist in a domestic setting. Her first novel, \'Stratford-by-the-Sea\', was published in 1884. It cemented Brown as part of the Boston literary scene, but by the time she died in 1948 (aged 91), many of her stories had been forgotten about and were no longer in print.